Avaliação de um sistema compacto de tratamento de água por osmose inversa aplicado em um trocador de calor - Macêdo, Alexandre Lopes de (Universidade Federal Rural do Semi-Árido, 2018)
Water is a fundamental substance for the survival of the society we know today, being used for both food and industry. In addition, it has a peculiar feature of dissolving substances that are exposed to it. Thus, it is necessary to use treatment processes so that it is possible to separate good quality water from the impurities according to the parameters required for the intended use. One of the most efficient forms of treatment is the reverse osmosis process and when coupled with other equipment as softeners, adequate water is obtained for equipment that uses thermal exchange as a principle. The work in question was concerned with analyzing and simulating a compact process of water treatment in the region of Mossoró-RN.
Monografia
Keywords: Água; Tratamento; Simulação; Osmose inversa; Trocador de calor; Water; Treatment; Simulation; Reverse osmosis; Heat exchanger; ENGENHARIAS::ENGENHARIA QUIMICA